Augusto Ruschi Biological Reserve vascular epiphytes: a hotspot in the mountains of the Atlantic Forest of Southeastern Brazil - Marcusso, Gabriel Mendes [UNESP]; Neto, Luiz Menini; Lombardi, Julio Antonio [UNESP] (Magnolia Press, 2022)
The Atlantic Forest (AF) is globally known as a hotspot of biodiversity, with high levels of endemism and richness. How-ever, within the AF, different localities may differ in their diversity values; in Southeastern Brazil, the mountainous region of Espirito Santo state is one of these highly biodiverse areas. Here, we present the first comprehensive checklist of the Augusto Ruschi Biological Reserve (ARBR) vascular epiphytes, a national protected area in the mountainous region of the state. Based on field expeditions carried out between 2018 and 2020 and extant herbarium collections, we reported a total of 359 species, 110 genera, and 20 families. Epidendrum henschenii Barb.Rodr. and Thysanoglossa organensis Brade are new records to the state. The richness recorded here is outstanding for the AF and one of the highest recorded in the Neotropical Region. The climatic conditions in the ARBR may help us understand this high species-richness, as well as the long-term climatic stability perhaps since the Miocene. Besides, the heterogeneity of the mountain habitats, driven mainly by erosion of the highlands since the early Cenozoic, resulted in the actual mountain's configuration of eastern Brazil, synchronously with most taxa diversification occurred in the Atlantic Forest. The present study demonstrated the importance of protected areas and pristine forests for the conservation and maintenance of biodiversity and the importance of floristic studies to fill knowledge gaps in the Atlantic Forest, mainly in mountainous regions.
Keywords: Checklist; Espírito Santo; Floristic; New records